Theoretical Study on Solubility from Pt Electrocatalyst and Reactivity in Electrolyte Environment of Pt Complex in PEFC - Takayoshi Ishimoto; Michihisa Koyama (International Journal of Electrochemistry)
We theoretically analyzed the formation energy and solvation free energy of Pt(II) and Pt(IV) complexes with three types of ligands (H2O, OH−, and CF3SO3 −) in electrolyte environment under the low- and high-humidity conditions to study the Pt electrocatalyst degradation and dissolution mechanisms for polymer electrolyte fuel cell. To represent the low- and high-humidity conditions in perfluorosulfonic acid (PFSA) polymer electrolyte membrane, we controlled the dielectric constant based on the experimental result. We observed general tendencies that the formation energy becomes larger while the solvation free energy becomes smaller under the low-humidity condition. The degradation of Pt complex from Pt surface is indicated to be accelerated by the adsorption of the end group of PFSA polymer side chain, on the Pt surface by comparing the desorption energies of [Pt(H2O)2(OH)3(CF3SO3)] and [Pt(H2O)2(OH)4]. The [Pt(H2O)4]2+ is not formed by the proton addition reaction between Pt complexes under the low-humidity condition of PFSA environment. From the analysis of possible reaction pathways of Pt complexes, we found the influence of humidity on the reactivity of Pt complex.